EVALUASI PENERAPAN KEBIJAKAN BADAN LAYANAN UMUM DAERAH DI RSUD UNDATA PROPINSI SULAWESI TENGAH - Laksono Trisnantoro, Surianto (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: One of the important things forchange is a sequentialcharacteristic or the phase of time for a change. Suchas the change stipulated by BLUD (Publis Service Agency)policy of the State Regional Hospital (RSUD) to become BLUD.The implementation of BLUD in the regional public hospital(RSUD) of Undata is generally based on the regulation of TheDepartement of Internal Affairs No 61 year 2007. The newparadigm as BLUD must be balancedof both the âEnterprisingthe Govermentâ and the âPublic Service Orientedâ. The backgroundof Undata Hospital before becoming BLUD were theproblem of health care cost was getting expensive whilst thetariffs imposed had to be competitive, and the demand of goodquality of services to care for the patients. All of this could beachieved if Undata hospital applies the financial managementsystem of the regional public service agency (PPK-BLUD).Method Of Research:Thisresearch uses a descriptive analysiswith the case study design. The samplings conducted inthis research are purposive sampling. Method of data colectionobtained through in depth interview, observation, utilization ofdocuments.Research Result: The implentation of regional public serviceagency (BLUD) based on the result of evaluation study inUndata hospital and in the health departement of CentralSulawesi Province shows that: The implementation based onthe standard, namely governance, business strategy plan,and the report of financial management has been implementedwell. Whereas the implementation which is not in accordanceyet with the BLUD criteria is the minimum service standardrelated to indicator and criteria of SPM. Also the role of healthdepartement as the supervisory board has yet to be implementedbecause there is no supervisory board.Conclusion: It shows the governance, business strategyplan and financial report are already in accordance with standard,set while the minimum service standard and the supervisoryboard have not run optimally within the standard andcriteria set.Key words: PPK-BLUD, implementation of BLUD, Hospital,Stakeholders